2018
DOI: 10.3389/fnhum.2018.00151
|View full text |Cite
|
Sign up to set email alerts
|

Motor Preparation Disrupts Proactive Control in the Stop Signal Task

Abstract: In a study of the stop signal task (SST) we employed Bayesian modeling to compute the estimated likelihood of stop signal or P(Stop) trial by trial and identified regional processes of conflict anticipation and response slowing. A higher P(Stop) is associated with prolonged go trial reaction time (goRT)—a form of sequential effect—and reflects proactive control of motor response. However, some individuals do not demonstrate a sequential effect despite similar go and stop success (SS) rates. We posited that mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…The OFC is involved in learning and optimal decisionmaking (57), encoding motivational salience of stimuli to support approach behavior (57,58), and integrating stimulus attributes and emotional value (59)(60)(61)(62). Part of the supplementary motor complex, the SMA is crucial to voluntary motor and cognitive control (63)(64)(65). Thus, these findings suggest greater male sensitivity to monetary reward, in accord with the literature.…”
Section: Sex Differences In Response To Feedback and Reward Sensitivitysupporting
confidence: 57%
“…The OFC is involved in learning and optimal decisionmaking (57), encoding motivational salience of stimuli to support approach behavior (57,58), and integrating stimulus attributes and emotional value (59)(60)(61)(62). Part of the supplementary motor complex, the SMA is crucial to voluntary motor and cognitive control (63)(64)(65). Thus, these findings suggest greater male sensitivity to monetary reward, in accord with the literature.…”
Section: Sex Differences In Response To Feedback and Reward Sensitivitysupporting
confidence: 57%
“…Finally, correlation analysis does not reflect directional interactions between brain regions. Research combining behavioral tasks with tools such as dynamic causal modeling and Granger causality analysis may reveal directional functional connectivities of the amygdala ( Ide and Li, 2011 ; Hu et al, 2015 ; Zhang et al, 2015 ; Sato et al, 2017 ; Zhang Y. et al, 2017 ; Velichkovsky et al, 2018 ; Wang et al, 2018 ). This research may also benefit from studies combining functional and spectroscopy imaging of neurotransmitters ( Delli Pizzi et al, 2017a , b ) and animal work that employs pharmacological manipulations to investigate the neurochemical mechanisms underlying amygdala interaction with other brain regions ( Andolina et al, 2013 ; Chang and Ho, 2017 ; Chang and Grace, 2018 ).…”
Section: Conclusion and Limitationsmentioning
confidence: 99%
“…The same brain regions showed higher activations proportionally to the extent to which participants anticipated conflict and slowed down in the stop signal task 49 , 56 , 78 . This finding suggested that individuals with higher Gf were more inclined to strategize their RT and the preSMA, right FPC and AI support these behavioral processes.…”
Section: Discussionmentioning
confidence: 85%